2020
DOI: 10.1016/j.heliyon.2020.e05531
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum IgG antibody titers against Porphyromonas gingivalis and liver enzyme levels: A cross-sectional study in Sado Island

Abstract: Background: Previous studies have reported associations between nonalcoholic fatty liver disease, periodontitis, and obesity. Serum immunoglobulin G (IgG) antibody titer against Porphyromonas gingivalis, a major pathogen of periodontitis, is an established indicator of periodontal infection. However, the relationship between the antibody titer and liver enzyme levels has not been clarified yet. A study in the elderly was needed to evaluate the effect of long-term persistent bacterial infection on liver functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…A previous study using multivariable linear regression analyses found that periodontitis is significantly associated with serum AST and ALT levels in healthy Japanese women (20–59 years old) [ 67 ]. In another previous study, a significant link between ALT level (68.5 ± 9.4 years old) and serum IgG antibody titer against P. gingivalis was identified in women, but not in men [ 68 ]. Moreover, in patients with NAFLD, no significant differences in serum ALT and AST levels were observed between patients with and without P. gingivalis detected in saliva [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study using multivariable linear regression analyses found that periodontitis is significantly associated with serum AST and ALT levels in healthy Japanese women (20–59 years old) [ 67 ]. In another previous study, a significant link between ALT level (68.5 ± 9.4 years old) and serum IgG antibody titer against P. gingivalis was identified in women, but not in men [ 68 ]. Moreover, in patients with NAFLD, no significant differences in serum ALT and AST levels were observed between patients with and without P. gingivalis detected in saliva [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Relevant information was obtained through comprehensive interviews with the participants when registering for PROST using a questionnaire encompassing covariates, such as smoking status, alcohol consumption, and disease history ( Supplement 1 ). As describe in a previous report from PROST [ 41 ], the responses to the questionnaire regarding smoking habit were as follows: (1) “I have a smoking habit,” (2) “I used to smoke but stopped,” and (3) “I do not smoke at all.” Past and present smokers were categorized into the “Have smoking habit” group. The responses for alcohol consumption were as follows: (1) “I drink more than 1 day a week,” (2) “I was a drinker before,” (3) “I'm a social drinker” and (4) “I do not drink alcohol at all.” Social drinkers and past drinkers were categorized into the “No drinking habits” and “Drinking habits” groups, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…[65] A cross-sectional study suggested an involvement between Pg infection and alanine ALT levels in women. [66] Intravenous injection of sonicated Pg creates glucose tolerance, insulin resistance, and fatty liver in mice fed high-fat diets. [67] A new-dated trial has investigated current periodontal treatment results within the possible changes in endotoxin levels and treat Pg infection to show the improvement status in NAFLD patients.…”
Section: Periodontal Problems and Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%